Police,crime and urban kano secruity. - Ali Ado Siro, Ali Ado Siro (Universiti Sains Malaysia, 2014)
Various researches have shown that police is the most important element in public security management (Williams & Williams, 2007; Sanders and Henderson, 2012; Kusha, 2013). In line with this, urban Kano as a cosmopolitan centre has some security issues related to crime and policing that need to be redressed (Ahmed et.al, 2013). For this purpose, secondary sources of data were used in the paper to address these issues with the aim of highlighting the true picture of the situation.